Capacities and phenomenological laws: for experimental disposiciontalism - Soto, Cristian; Rodríguez, Pascal (Revista de Filosofía, 2019)
We elaborate a form of experimental dispositionalism that illuminates the relationship between capacities and phenomenological laws. After some introductory remarks (1), we introduce experimental dispositionalism in view of the notions of physical modality and environment of stimulus (2). Such notions are crucial for both outlining an experimental epistemology for capacities (3) and understanding the physical modality and invariance of phenomenological laws (4). We characterize physical generalizations and extrapolations licensed by phenomenological laws (5), and examine the Fresnel law, which illustrates key elements of our argument (6). We close with remarks on the scope and limits of experimental dispositionalism (7).